2014
DOI: 10.1108/ijebr-10-2012-0111
|View full text |Cite
|
Sign up to set email alerts
|

Stimulating learning about social entrepreneurship through income generation projects

Abstract: Abstract:Purpose -This empirical paper examines the use of income generation projects as a pedagogic method to assess students' learning about social enterprises. We are interested in how and why this innovative approach might improve students' understanding of the different aspects and attributes of social entrepreneurship.Design/methodology/approach -our study used thematic analysis of qualitative data comprising the reflective logs of 87 students on an undergraduate entrepreneurship module in a university b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 69 publications
0
9
0
2
Order By: Relevance
“…Funding might be captured through revenues or external resources and must sustain the enterprise in a way that is aligned with its proposal. It can be accessed through private or public institutions, or collaboration with available social networksalthough the dependence on external financing might lead to a competition for resources, which undermines the possibility of building cooperation networks (Ahlberg et al, 2016;Chang et al, 2014;Margarian, 2017;Ochman, 2019).…”
Section: Csf and Enablersmentioning
confidence: 99%
“…Funding might be captured through revenues or external resources and must sustain the enterprise in a way that is aligned with its proposal. It can be accessed through private or public institutions, or collaboration with available social networksalthough the dependence on external financing might lead to a competition for resources, which undermines the possibility of building cooperation networks (Ahlberg et al, 2016;Chang et al, 2014;Margarian, 2017;Ochman, 2019).…”
Section: Csf and Enablersmentioning
confidence: 99%
“…They emphasized that it is important to consider the significant impact of moderators, such as the attributes of entrepreneurship education, differences between students, and cultural values, on entrepreneurial intentions. Most studies suggest a positive link between the educational program and students' entrepreneurial intentions, attitude, knowledge, and skills [84][85][86][87], but some articles report results that are not significant or negative. For example, Lanero, et al [88] reported that there is no significant link between entrepreneurship education and entrepreneurial attitudes among Spanish students.…”
Section: Comparison Based On Educational Experiences In Entrepreneurshipmentioning
confidence: 99%
“…Esta seção retrata as agendas de pesquisa formuladas por autores dos artigos analisados nesta revisão de literatura. As agendas mais recorrentes mencionam a necessidade de se estudar os métodos de ensino em empreendedorismo social e, em especial, a aplicação da Aprendizagem Experiencial e a Aprendizagem em Serviço (Chang et al 2014;Kedmenec et al, 2016;Mueller et al, 2015;Yann et al, 2014;Bacq & Alt, 2018;Hockerts, 2018;Ashour, 2016;Greblikaite et al, 2016) , identificar e relacionar melhor os efeitos das variáveis etnia, idade, sexo, familiaridade com tecnologia, experiência social, experiência de trabalho, normas subjetivas, empatia, antecedentes do valor social, autoeficácia, barreiras da intenção de empreendedorismo social, formação da intenção empreendedora social, traço de personalidade, criatividade, motivação, capital social, efeito do estilo cognitivo (Yann et al, 2014;Tiwari et al, 2017;Tiwari et al, 2017;Tiwari et al, 2017;Hockerts, 2017;Bacq & Alt, 2018;Shahverdi et al, 2018;Hsu & Wang, 2018;Mueller et al, 2015).…”
Section: Lacunas E Agenda De Pesquisaunclassified
“…Foram sugeridas mais pesquisas sobre o efeito das abordagens de Aprendizagem Experiencial e a Aprendizagem em Serviço para buscar entender as experiências dos acadêmicos em lidar com esta forma metodológica (alunos e professores), verificando também as visões dos outros interessados (comunidade, organizações e empreendedores sociais), especialmente para descobrir como eles se beneficiam desse tipo de abordagens. (Yann et al, 2014;Chang et al 2014;Bacq & Alt, 2018).…”
Section: Lacunas E Agenda De Pesquisaunclassified